2010
DOI: 10.1183/09031936.00006710
|View full text |Cite
|
Sign up to set email alerts
|

Steroids in COPD: still up in the air?: Fig. 1—

Abstract: Inhaled corticosteroids (ICS) have had a wild and controversial rollercoaster ride in chronic obstructive pulmonary disease (COPD). With the success of ICS in asthma and with the advent of the Dutch Hypothesis, suggesting that asthma and COPD had a similar pathogenic origin, there was great hope that ICS would be the saviour for millions of patients suffering from COPD, by palliating symptoms and changing its natural history. Based on this promise, by the mid 1980s, clinicians were routinely recommending ICS t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Exactly what benefits COPD patients can hope for from regular treatment with ICS remains controversial [21] and a discussion on this issue goes well beyond the scope of this study which aimed to investigate the consequence of ICS withdrawal in “low-risk” COPD patients. We acknowledge that the lack of randomization is a major limitation of this study and that we cannot draw a definitive conclusion which requires a randomized controlled trial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exactly what benefits COPD patients can hope for from regular treatment with ICS remains controversial [21] and a discussion on this issue goes well beyond the scope of this study which aimed to investigate the consequence of ICS withdrawal in “low-risk” COPD patients. We acknowledge that the lack of randomization is a major limitation of this study and that we cannot draw a definitive conclusion which requires a randomized controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…It cannot be said therefore that doctors, and even specialists, fail to follow the guidelines due to a lack of available information. There are other explanations which need to be investigated [21]. It seems not to be a problem specific to a single country such as Italy: in the multi-centric and multi-country ECLIPSE [27] and UPLIFT studies [30], about 60% of patients in GOLD stage 2 were treated with ICS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early hopes that they would improve quality of life (QoL) have not been confirmed[8]. Although statistically significant improvements in QoL scores have been shown in some large trials of combined ICS and LABA, none has shown an improvement reaching the minimal clinically important difference (MCID) of the instrument used[9-16].…”
Section: Introductionmentioning
confidence: 99%
“…In only three trials has the upper limit of the 95% confidence interval of the improvement in intervention group patients reached the MCID[11,14,15]. Disappointed in the lack of evidence [6,8] Sin and Man in 2010 made the questionable suggestion that “A more plausible (and simple) explanation (for the high worldwide sales of combined ICS/LABA) is that clinicians (and patients) use ICS-based therapy for COPD because they work”. [8] Discussion of the role of ICS in symptom management of COPD was notable by its absence in the recent Lancet review by Rabe and Wedzicha[17].…”
Section: Introductionmentioning
confidence: 99%